2021
DOI: 10.1155/2021/1519904
|View full text |Cite|
|
Sign up to set email alerts
|

Change of Levels of NGF, ACTH, and AVP in the Cerebrospinal Fluid after Decompressive Craniectomy of Craniocerebral Injury and Their Relationship with Communicating Hydrocephalus

Abstract: In recent years, the incidence of craniocerebral trauma has increased, making it one of the important causes of death and disability in neurosurgery patients. The decompressive craniectomy (DC) after severe craniocerebral injury has become the preferred treatment for patients with severe craniocerebral injury, but the incidence of postoperative hydrocephalus has become a difficult problem in clinical treatment. This study observed the changes of nerve growth factor (NGF), adrenocorticotropic hormone (ACTH), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…From the clinical definition, hypothermia is currently divided into the following 4 degrees internationally: Mild hypothermia is 33°C to 35°C; Moderate hypothermia is 28°C to 32°C; Profound hypothermia is 17°C to 27°C; Ultraprofound hypothermia is below 16°C. [6] The experts from various countries call mild and moderate hypothermia as mild hypothermia. Some animal control studies found that the curative effect of mild hypothermia at 30°C was better than that at 33°C.…”
Section: Introductionmentioning
confidence: 99%
“…From the clinical definition, hypothermia is currently divided into the following 4 degrees internationally: Mild hypothermia is 33°C to 35°C; Moderate hypothermia is 28°C to 32°C; Profound hypothermia is 17°C to 27°C; Ultraprofound hypothermia is below 16°C. [6] The experts from various countries call mild and moderate hypothermia as mild hypothermia. Some animal control studies found that the curative effect of mild hypothermia at 30°C was better than that at 33°C.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%